2013
DOI: 10.1096/fj.13-237578
|View full text |Cite
|
Sign up to set email alerts
|

In situ intracellular calcium oscillations in osteocytes in intact mouse long bones under dynamic mechanical loading

Abstract: Osteocytes have been hypothesized to be the major mechanosensors in bone. How in situ osteocytes respond to mechanical stimuli is still unclear because of technical difficulties. In vitro studies have shown that osteocytes exhibited unique calcium (Ca(2+)) oscillations to fluid shear. However, whether this mechanotransduction phenomenon holds for in situ osteocytes embedded within a mineralized bone matrix under dynamic loading remains unknown. Using a novel synchronized loading/imaging technique, we successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 61 publications
8
113
1
Order By: Relevance
“…We recently modified the ex vivo system described earlier to observe Ca 2þ responses in live osteocytes in a mouse long bone subjected to dynamic, deformational loading (figure 2a). Osteocytes exhibited robust oscillations in Ca 2þ in response to load in a load-dependent manner (figure 2b) [79]. This pattern was more pronounced than the autonomous Ca 2þ responses of osteocytes, which were undetectable, as well as the loadinginduced and autonomous responses of cells on the bone surface (figure 2b) [76,79].…”
Section: Mechanosensation and Early Mechanotransduction In Osteocytesmentioning
confidence: 98%
“…We recently modified the ex vivo system described earlier to observe Ca 2þ responses in live osteocytes in a mouse long bone subjected to dynamic, deformational loading (figure 2a). Osteocytes exhibited robust oscillations in Ca 2þ in response to load in a load-dependent manner (figure 2b) [79]. This pattern was more pronounced than the autonomous Ca 2þ responses of osteocytes, which were undetectable, as well as the loadinginduced and autonomous responses of cells on the bone surface (figure 2b) [76,79].…”
Section: Mechanosensation and Early Mechanotransduction In Osteocytesmentioning
confidence: 98%
“…Recent research has also shown the real-time Ca 2+ oscillations in response to a direct mechanical stimulation on an intact ex vivo mouse tibia [31]. However, the Ca 2+ oscillation pattern has not been identified through fluid flow alone mechanism, in the absence of mechanical strain, until this study, which can be achieved with a direct DFFS into the marrow cavity of an intact ex vivo mouse long bone to generate fluid shear.…”
Section: Discussionmentioning
confidence: 90%
“…For Ca 2+ fluorescent labeling, the bone samples were incubated for 2 hours in 15 μM Fluo-8 AM (Santa Cruz Biotechnology, Inc., Dallas, Texas, U.S.A.) dissolved in dimethyl sulfoxide (DMSO) and culture medium before confocal imaging [31]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteocytes subjected to mechanical stimulation respond rapidly by mobilizing a series of second messengers, including calcium [59,60], nitric oxide [61,62], and prostaglandins [63]; by activating kinase signaling cascades, including the MAP kinase and PKC pathways [64]; and by exhibiting alterations in gene expression [65]. In addition, osteocytes respond to biophysical cues by releasing soluble factors important for cellular proliferation and differentiation and for recruitment of osteoblasts and osteoclasts [66][67][68][69][70].…”
Section: Osteocytes As the Master Regulator Of Load-induced Bone (Re)mentioning
confidence: 99%